Diet modulates the relationship between immune gene expression and functional immune responses. (June 2019) - Cotter, Sheena C.; Reavey, Catherine E.; Tummala, Yamini; Randall, Joanna L.; Holdbrook, Robert; Ponton, Fleur; Simpson, Stephen J.; Smith, Judith A.; Wilson, Kenneth
Abstract: Nutrition is vital to health and the availability of resources has long been acknowledged as a key factor in the ability to fight off parasites, as investing in the immune system is costly. Resources have typically been considered as something of a "black box", with the quantity of available food being used as a proxy for resource limitation. However, food is a complex mixture of macro- and micronutrients, the precise balance of which determines an animal's fitness. Here we use a state-space modelling approach, the Geometric Framework for Nutrition (GFN), to assess for the first time, how the balance and amount of nutrients affects an animal's ability to mount an immune response to a pathogenic infection. Spodoptera littoralis caterpillars were assigned to one of 20 diets that varied in the ratio of macronutrients (protein and carbohydrate) and their calorie content to cover a large region of nutrient space. Caterpillars were then handled or injected with either live or dead Xenorhabdus nematophila bacterial cells. The expression of nine genes (5 immune, 4 non-immune) was measured 20 h post immune challenge. For two of the immune genes (PPO and Lysozyme) we also measured the relevant functional immune response in the hemolymph. Gene expression and functional immune responses were then mapped against nutritional intake. The expression of all immune genes was up-regulated by injection with dead bacteria, but only those in the IMD pathway (Moricin and Relish) were substantially up-regulated by both dead and live bacterial challenge. Functional immune responses increased with the protein content of the diet but the expression of immune genes was much less predictable. Our results indicate that diet does play an important role in the ability of an animal to mount an adequate immune response, with the availability of protein being the most important predictor of the functional (physiological) immune response. Importantly, however, immune gene expression responds quite differently to functional immunity and we would caution against using gene expression as a proxy for immune investment, as it is unlikely to be reliable indicator of the immune response, except under specific dietary conditions. Graphical abstract: Image 1 Highlights: High protein diets improved survival after live bacterial infection. Injection with dead bacteria increased expression of Toll and IMD immune genes. Injection with live bacteria inhibited immune gene expression (GE). The ratio and concentration of macronutrients in the diet affected GE. GE only predicted functional immune activity at high levels of dietary protein.